IMPLEMENTASI PEMBERIAN PERLINDUNGAN HUKUM TERHADAP PELAKU WHISTLEBLOWER PADA TINDAK PIDANA KORUPSI DI KOTA PEKANBARU - Aviska Loveana Tomanda; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The role of the whistleblower is very large to protect the country from more severe losses and violations of the law that occur. But the risks they face are also great when exposing crime, ranging from threats to security to being expelled from the agencies where they work. So the Whistleblower is important to get legal protection from the state. In recent cases there have been many whistleblower witnesses who withdrew their reports or testimonies because of threats and intimidation from the reported parties. This is because the implementation of providing legal protection for whistleblowers has not yet been implemented. Based on this fact, there are two problem formulations in writing this thesis, namely; First, the implementation of the form of providing legal protection for whistleblowers in corruption in Pekanbaru. Second, obstacles in the implementation of the provision of legal protection against whistleblowers in corruption in Pekanbaru.This type of research can be classified in the type of sociological legal research, because in this study the authors directly conduct research at the location under study in order to provide a complete and clear picture of the problem under study. This research was conducted at the Special Criminal Directorate of the Riau Regional Police, while the population and sample were all parties related to the problem under study, data sources used, primary data and secondary data, data collection techniques in this study were interviews and literature studies.From the results of the analysis of the problem it can be concluded first, the implementation of granting legal protection against whistleblowers in corruption in Pekanbaru is still very alarming where, the police have not been able to coordinate well with authorized institutions in this case LPSK in providing protection against whistleblowers so that many witnesses whistleblower retracts its report due to various threats from the reported party. Second, obstacles faced by the Riau Regional Police in implementing witness protection include the difficulty in administering the system to the LPSK (Witness and Victim Protection Agency), the budgetary factor for managing witness protection and the lack of witness and / or victim knowledge of the witness and victim protection law. From this analysis the authors suggest, first, the whistleblower must obtain adequate protection from the authorized institution. Second, good cooperation between law enforcers and authorized institutions is needed to ensure the legal protection of whistleblowers.Keywords: Implementation - Protection - Witnesses and Victims - Whistleblowers